Supply chain security: an integrated framework for container terminal facilities. (1st January 2012) - Longo, Francesco
The goal of this paper is to present an ongoing research programme at Modelling and Simulation Center, Laboratory of Enterprise Solution (MSC-LES). The Security Advances in marine PORTS (SEAPORTS) research programme presents an advanced simulation framework for investigating and analysing security problems within marine ports environments (specifically container terminals) to find out security gaps and proceed with redesign of the most critical security procedures and infrastructures.